Pathological Features of Bovine Pericardium Implanted Into Mice Abdominal Wall after Preservation with Glutaraldehyde or Glycerin - Costa, Cláudia Borges; Silva, Marta Fernanda Albuquerque da; Andrade, Gisele Braziliano de (Acta Scientiae Veterinariae, 2016)
Background: Lately, the use of biological materials has been widely indicated in surgical procedures to restore structure and function of injured tissues. Bioimplants require different conservation techniques; among these, glutaraldehyde preservation stands out owing to its higher antimicrobial efficiency as compared to glycerin. In view of the need to determine a concentration of glutaraldehyde that can act as a biocide but do not cause undesirable tissue reactions, this study aimed to identify and quantify gross and microscopic tissue alterations after implantation of bovine pericardium, which was preserved in various concentrations of glutaraldehyde, in the abdominal wall of mice. Materials, Methods & Results: Fresh pericardia from 18 bovines were fractioned into 1cm2 samples and treated with a 98% glycerin solution for 30 days (control group), or 0.625%, 1%, and 1.5% glutaraldehyde solution for 18 days (experimental groups). An abdominal muscle fragment was excised from each mouse, and a 1-cm2 fragment of preserved pericardium was implanted in the area. Sixty mice (n = 15 per treatment) divided into groups were observed for 7, 14, and 30 days, and five animals from each group were euthanized at each time point for gross and microscopic examination. Fragments of the implants and adjacent skin lesions were harvested, fixed in formalin, and processed for routine histology and microscopic analysis. Both the type of inflammatory infiltrate and the repair process of the tissue response were similar between the groups that received glycerin-preserved pericardium and those that were subjected to pericardium preserved with 0.625% glutaraldehyde. Animals that received 1% glutaraldehyde-preserved implants and were examined 30 days thereafter exhibited a chronic, intense reaction with fibrosis and necrosis of the abdominal wall muscles, as well as calcification and presence of giant cells, when compared to the animals examined at 7 and 14 days in the same treatment group. These changes were also present and more intense in animals that received 1.5% glutaraldehyde-preserved pericardium examined at 14 and 30 days later, with tissue destruction and impaired incorporation of the implant into the adjacent muscle tissue. Discussion: The continuous cell destruction observed in animals treated with implants preserved with 1% or 1.5% glutaraldehyde is a hallmark of chronic inflammation, since several inflammatory cell molecules contribute to this lesion. A cycle is created: continuous degradation sustains inflammation, and inflammatory molecules contribute to the process of cell destruction. Consequently, we conclude that the use of glutaraldehyde at concentrations of 1 or 1.5% is not feasible for preservation of biological materials. Tissue repair was chronologically more effective in the group treated with glycerinpreserved implants, since animals treated with glutaraldehyde-preserved implants needed a longer period to restore due to presence of a persistent inflammatory response, immunogenicity, calcification, and deficient remodeling. The ideal preservative for biological materials should not cause chronic and/or intense inflammatory reaction in order to preserve the implant’s structure and allow its perfect incorporation into the tissue, even if the chosen preservative is flexible and exhibits disinfectant properties. Therefore, we conclude that glutaraldehyde at concentrations of 0.625% to 1% is suitable as a preservative for biomaterials because the tissue reaction it causes is tolerable; additionally, glutaraldehyde at concentrations close to 1% has been described to have sterilizing properties.